Effect of Tillage Depth on Infiltration Characteristics, Erosion control and Resultant Crop Yield in Red soils of Bundelkhand - Nitant, H.C. (Journal of Soil and Water Conservation, 2022)
Runoff plots were established on a shallow gravelly soil having In the semi-arid tropics of India to eomparted evaluate the effect of tillage treatments viz., shallow tillage by using country plough (CP) 10 cm deep, deep tillage with mouldboard (MB) 20 cm deep and by using sub-soiler (SS) 40 cm deep on infiltration characteristics erosion control and yield of redgram and sorghum under thyland conditions under two rain all seasons in 1990 and 1991. Deep tillage treatment SS tremendously increased the cumulative infiltration and steady infiltration rate with greater profile water storage by controlling runoff loss than other tillage treatments (MB and CP), Thus the highest infiltration rate 3.0 and 3.8 cm was recorded in plots tilled with subesoiler for planting redgram and sorghum, respectively. It also (SS) resulted in maximum profile water storage. Consequently least runoff (32 and 28% in redgram and 31 and 26% in sorghum in 1990 and 1991, respectively) was recorded. As a result, highest grain to a quantum of 1272 and 840 kg/ha redgram and 2508 and 1308 kg/ha sorghum was produced due to deep tillage treatment (SS) as against lowest grain production to 642 and 543/ha redgram and 1339 and 802 kg/ha sorghum in 1990 and 1991, respectively, obtained in shallow tillage treatment (CP). This is attributed downward water movement in soil due to existence of compacted layer in sub-soil and thereby maximum runoff (41-48N was registered from shallow tilled plots (CP). However, mouldboard ploughing (MB) gave moderate results.